Comparative Pharmacokinetic Studies of Four Ginsenosides in Rat Plasma by UPLC-MS/MS after Oral Administration of Panax quinquefolius-Acorus gramineus and Panax quinquefolius Extracts - Hailong Xie; Dongxue Wang; Wenjun Zhang; Xinjia Yan; Ying Zhao (Journal of Analytical Methods in Chemistry)
Panax quinquefolius (PQ) and Acorus gramineus (AG) are drug target pairs in traditional Chinese medicine (TCM), which are used to treat age-related diseases. In the present study, we simultaneously determined the contents of four main bioactive ginsenosides (Rb1, Rb2, Rd, and Re) in rat plasma using an ultrahigh-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method. Plasma specimens were purified by using the solid-phase extraction procedure, and separation was performed on Waters ACQUITY UPLC BEH C18 (100 mm × 2.1 mm, 1.7 μm) in multiple reaction monitoring (MRM) mode and negative electrospray ionization (ESI) mode. The established UPLC-MS/MS method showed good linear correlation (r ≥ 0.9978), stability (−11.93 to 12.11%), precision (RSD < 14.63%), and recovery (76.43%–95.20%). The lower limit of quantification was 3.6 ng/mL for Rb1, 1.6 ng/mL for Rb2, 1.2 ng/mL for Rd, and 2.5 ng/mL for Re. This validated method was successfully employed to investigate the pharmacokinetics of the four ginsenosides in rat plasma after oral administration of PQ-AG and PQ extracts. The results revealed the pharmacokinetic profiles of PQ-AG drug pair and clarified that AG played a critical role in stimulating the absorption of active ginsenosides in PQ. Collectively, our findings provided valid and reliable evidence for the rational use of PQ-AG in clinical practice.